Potentials of saponins-based adjuvants for nasal vaccines - Chen, Kai; Wang, Ning; Zhang, Xiaomin; Wang, Meng; Liu, Yanyu; Shi, Yun (Frontiers in Immunology, 2023)
Respiratory infections are mainly caused by pathogens colonizing and invading the respiratory mucosal surface. Nasal vaccines have the potential advantage of providing protection at the primary site of pathogen infection, with induction higher levels of mucosal secretory IgA antibodies and antigen-specific T and B cell responses. Adjuvants are important parts of vaccine formulation together with antigens and function to enhance the immunogenicity of the co-inoculated antigen with the aim of conferring long-term and effective protection. Saponins derived from plants are natural glycosides of steroids or triterpenoids with abilities to activate the mammalian immune system, leading great interest to their potential as a vaccine adjuvant. Saponins-based adjuvants are used in several licensed vaccines for human use administrated by intramuscular injection, showing good efficacy and safety. Currently, many studies have shown that saponins have the potentials to be used as adjuvants for nasal vaccines. Due to its safety and potential adjuvant effects in mucosal immune response, we believe that saponins-based adjuvants have good potentials used in nasal vaccines to elicit good mucosal and systemic immune response to co-administrated antigens. Herein, we will elucidate the structure-activity-relationship of saponins, the essential role of saponin-derived adjuvants in nasal vaccines and discuss their perspective studies area for respiratory infections.